Village Asset Utilization Policy to Increase Village Original Income - Dyah Andriani Saraswati; Sukardi; Saudah (Innovation Business Management and Accounting Journal, 2025)
study aims to analyze the implementation of the village asset utilization policy in increasing village revenue and identify the inhibiting factors based on Blitar Regent Regulation Number 55 of 2019. The research location was Binangun Village. The data analysis technique in this study used the descriptive-analytic method. This study found that implementing the village asset utilization policy in Binangun Village based on Blitar Regent Regulation Number 55 of 2019 still faces various obstacles. Policy communication has not covered the entire community, especially regarding utilizing southern kiosks. Human resources do not have a deep understanding, causing important stages such as market price surveys and agreement documents not to be carried out. Supporting regulations such as Village Regulations (Perdes) on Village Market Management and Village Head Regulations (Perkades) on Utilization of Village-Owned Land for Official Use, also known as Village Bengkok Assets, have not been prepared. At the same time, incentives for asset managers have not been provided due to differences in regulations and budget constraints. In addition, the unavailability of SOPs has led to inconsistencies with applicable regulations. Supporting factors include the commitment of the village government and the use of SIPADES. In contrast, barriers include the lack of supervision, leadership assertiveness, and community participation in utilizing village assets. This research contributes to policy implementers in improving socialization, training of asset managers, drafting regulations, policy enforcement, and coordination with the Inspectorate and Village Consultative Body (BPD) to optimize the utilization of village assets to increase Village Original Income.